2022
DOI: 10.1123/jsr.2021-0056
|View full text |Cite
|
Sign up to set email alerts
|

Interrater Reliability of an Observational Rating Scale and Video Analysis of Yoga Poses

Abstract: Context: Yoga is increasingly popular, not only as a form of recreational exercise but also as a physician-recommended intervention for health conditions. While serious adverse effects accompanying yoga practice are rare, poses that involve upper-extremity weight-bearing have a high risk of discomfort. To better understand factors contributing to adverse effects, there is a critical need for robust instruments that objectively evaluate pose performance. The purpose of this study was to assess the interrater re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
0
0
Order By: Relevance
“…Mir Fatemeh explored the effects of different content, forms, and physiological loads of yoga and aerobic exercise on improving athlete physical fitness, and the results showed that long-term yoga practice was effective in improving athlete physical conditions [ 10 ]. Richmond Diane said that although yoga does not play an important role in improving the metabolism of athletes, it played a significant role in developing flexibility, strength, and reducing physical fatigue [ 11 ]. Phuhanich Melissa E pointed out that yoga exercise can help stretch the muscles of the body, increase the range of motion of the joints, and promote the flexibility and endurance of all parts of the body [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mir Fatemeh explored the effects of different content, forms, and physiological loads of yoga and aerobic exercise on improving athlete physical fitness, and the results showed that long-term yoga practice was effective in improving athlete physical conditions [ 10 ]. Richmond Diane said that although yoga does not play an important role in improving the metabolism of athletes, it played a significant role in developing flexibility, strength, and reducing physical fatigue [ 11 ]. Phuhanich Melissa E pointed out that yoga exercise can help stretch the muscles of the body, increase the range of motion of the joints, and promote the flexibility and endurance of all parts of the body [ 12 ].…”
Section: Introductionmentioning
confidence: 99%